Loss and Grief Among Bereaved Family Members During COVID-19 in Brazil: A Grounded Theory Analysis - Paola Kallyanna Guarneri Carvalho de Lima; Carlos Laranjeira; Lígia Carreira; Vanessa Denardi Antoniassi Baldissera; Viviani Camboin Meireles; Wanessa Cristina Baccon; Lashayane Eohanne Dias; Amira Mohammed Ali; Fernanda Fontes Mello; Maria Fernanda do Prado Tostes; Maria Aparecida Salci (Behavioral Sciences)
The COVID-19 pandemic has resulted in countless losses around the world, profoundly affecting the lives of many people, especially those who faced the death of family members, bringing several negative repercussions to these families and constraining the experience of grief. This study aimed to understand the experience of loss and grief among bereaved individuals who lost family members during the COVID-19 pandemic. This qualitative study was guided by Charmaz’s constructivist grounded theory as a methodological framework. The study adhered to the Criteria for REporting Qualitative research (COREQ) checklist. Data collection took place between May and November 2023 through telephone interviews that were audio-recorded and later transcribed in full. The purposive sample consisted of 21 bereaved family members who had lost their loved ones during the COVID-19 pandemic. Participants were mainly female (n = 16) with a mean age of 55.5 (SD = 16.2). The loss of their family members occurred 12 to 24 months before data collection. The following central phenomenon was identified through the analytical process: “Family experience of loss and grief: between the unspoken goodbye and post-loss adjustment”. This was anchored in the following three categories: (1) Anguish and fear of the unknown; (2) Death by COVID-19—communication of death and lack of goodbyes; and (3) (Re)construction of meaning—support networks and the grieving process. Our findings recommend that policymakers allocate additional resources to grief support services to better prepare for future pandemic events. Furthermore, it is necessary to invest in the implementation of relevant training programs for healthcare professionals, with a family centered approach.